ANALISIS PERAN GURU DALAM MENGOPTIMALKAN IMPLEMENTASI KURIKULUM MERDEKA - Nor Hapipah; Mirna Astuti; Suci Skar Kinanti; Farahah Kamilatun Nuha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted to examine more deeply the role of teachers in maximizing the implementation of the independent curriculum at SDN 7 Palangka Raya. The independent curriculum itself aims to provide freedom to students in learning both choosing learning methods this is an evaluation of the previous 2013 curriculum. However, for this to work, it cannot be separated from the role of the teacher as a facilitator. The purpose of this study was to reveal teacher perceptions about optimizing the independent curriculum in elementary schools. This research method uses qualitative research by collecting data through interviews. The research location is at State Elementary School 7 Palangka Raya. Data analysis techniques use data collection, data reduction, data presentation, conclusion drawing and verification. The instrument used was an interview sheet. The results showed that to maximize the role of the teacher requires, teacher expertise as a facilitator in supporting the learning process so that learning runs according to learning objectives. Teachers have a role in exploring the interests of each learner. Teachers provide more support for the achievements of individual students. So the role of the teacher is very urgent in the learning process. Teachers are responsible for the success or failure of learning because teachers not only transfer knowledge but more than that teachers must transfer good character. Because students will follow whatever the teacher exemplifies.